In situ Raman spectroscopy of carbon nanotube growth by chemical vapor deposition - Li-Pook-Than, Andrew (University of Ottawa (Canada), 2010)
In situ Raman spectroscopy was used to track the growth of carbon nanotubes grown by chemical vapor deposition. The dynamic evolution of three kinds of Raman bands, namely the G, D, and RBM bands, was analyzed. The evolution of nanotube diameter and crystallinity was analyzed from the RBM and D/G band evolution, respectively. A characteristic growth sequence consisting of four distinct stages of growth was consistently observed. The growth rate of each stage was found to decrease with increasing temperature, possibly due to parasitic, competing reactions, and energy scales for each stage are extracted. The evolution and nanotube distribution of samples grown with and without alumina support layers is contrasted and the role of alumina is discussed.
Keywords: Physics, Condensed Matter.; Physics, Optics.